A new Nactus gecko (Gekkonidae) and a new Leiolopisma skink (Scincidae) from La Reunion, Indian Ocean, based on recent fossil remains and ancient DNA sequence - Arnold, E. Nicholas; Bour, Roger (Zootaxa, 2008)
Two new lizards from La Réunion island, southwest Indian Ocean, are described on the basis of fragmentary subfossil material, and their distinctiveness and relationships are confirmed from ancient mitochondrial DNA extracted from these remains. The gecko Nactus soniae n. sp. is related to N. coindemerensis of Mauritius, while the skink Leiolopisma ceciliae n..sp. .has affinities with L. telfairii and L. mauritiana from the same island. As with other La Réunion reptiles known to date, mitochondrial DNA phylogenies indicate that both the new forms colonized this island from Mauritius. Molecular clock considerations suggest that colonisations took place over 1My ago and that the new species, together with Phelsuma day geckos, survived the massive volcanic eruptions that took place on La Réunion 180000-230000 years ago.